Exploring Digital Learning Support to Foster EFL Student Interests in Indonesian Higher Education - Shafa, Shafa; Paramma, Muhammad Azwar; Noor, Widya Noviana; Kordja, Baharuddin (Institut Agama Islam Negeri Palopo, 2023)
Developments in education highlight the need for conventional learning approaches to evolve in response to technological advances in digitally integrated learning, including hybrid or digital learning approaches. Digital-based teaching in higher education has begun to be implemented comprehensively, although it is still full of challenges. This study aims to determine students’ learning interest in digital-based instruction in the universities of East Kalimantan. It employed a purposive sample of 91 EFL students in their second and fourth semesters. This study reveals the potential for implementing digital-based instruction to support the increased interest in learning among EFL students in universities. It demonstrates the significance of digital learning as an adaptation of technological educational advances. However, implementing digital instruction in higher education is not effortless for students as end-users. Numerous students are resistant and unable to adjust to the shift towards online and digital learning. They tend not to participate actively in class and even ignore the material and assignments given. Therefore, these findings contribute to advancing future research on digital learning. They will also strengthen developments in digital learning based on user requirements and the learning context. In light of these findings, stakeholders in higher education need to make efforts to adjust the digital-based instruction applied to students’ abilities and needs, as well as the context of the lectures being held. Further research is required to incorporate a broader range of substantial participants and diverse data in order to attain a more comprehensive understanding of students’ learning interest in digital learning.